Two-dimensional photonic crystals in antimony-based films fabricated by holography - Nalin, M. [UNESP]; Menezes, J. W.; Cescato, L.; Braga, E. S.; Hernandez-Figueroa, H.; Ribeiro, S. J. L. [UNESP]; Messaddeq, Y. [UNESP]; Li, M. Siu (American Institute of Physics (AIP), 2008)
In this work, we demonstrated the fabrication of two-dimensional (2D) photonic crystals layers (2D-PCLs) by combining holographic recording and the evaporation of antimony-based glasses. Such materials present high refractive indices that can be tuned from 1.8 to 2.4, depending on the film composition; thus, they are interesting dielectric materials for fabrication of 2D-PCLs. The good quality of the obtained samples allowed the measurement of their PC properties through the well-defined Fano resonances that appear in the transmittance spectrum measurements at different incidence angles. The experimental results are in good agreement with the calculated band diagram for the hexagonal asymmetric structure. (C) 2008 American Institute of Physics.